Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences